Ineffective Pelvic Magnetic Resonance Imaging for the Detection of a Levonorgestrel-releasing Intrauterine System Straying into the Abdominal Cavity - Kensuke Ogino; Hiroe Ito; Koji Fujimori; Junko Nakagawa; Keiichi Isaka; Yasufumi Oishi (Gynecology and Minimally Invasive Therapy)
The levonorgestrel intrauterine system (LNG-IUS) is used by patients for dysmenorrhea, but cases of uterine perforation have been observed. This patient underwent replacement 5 years after the initial LNG-IUS insertion, but persistent abdominal pain led to a visit to her previous gynecologist. Transvaginal ultrasonography and magnetic resonance imaging (MRI) at the time of the visit did not detect LNG-IUS. A subsequent computed tomography (CT) scan clearly showed the entire T-shape of the LNG-IUS on the sagittal plane and revealed the presence of the LNG-IUS in the abdominal cavity. Laparoscopic observation revealed that the adhesion of the LNG-IUS was mild, and it could be removed without damaging other organs. The patient was discharged without problems on the third postoperative day. LNG-IUS extraction via ultrasonography and MRI is considered challenging due to its material characteristics. We report a case of intrabdominal LNG-IUS migration where CT and X-ray proved useful in the localization of LNG-IUS.